The Mediating Effect of Brand Image on Behavioral Intention, Social Media Sales Promotion Content, and Corporate Reputation (Study on Lion Air Customers) - Rahma, Deshinta Raisa; Sudarmiatin, Sudarmiatin; Dhewi, Titis Shinta (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The use of social media has change companies began to build communications with customers through social media. Lion Air is one of the companies who used social media to introducing the products. This study focused to investigate the effect of social media sales promotion content (SMSPC) and corporate reputation (CR) on behavioral intention (BIY) through brand image (BI). There are 7 hypotheses on this research and analysis using Partial Least Square (PLS). The samples for this research were respondents who followed Instagram @lionairgroup and has used Lion Air Airlines service using non-probability sampling technique. The result of this research shows that brand image as a mediation can decrease the value of consumers behavioral intention on Lion Air customers. The results of this investigation offer both theoretical insights and empirical evidence that can be beneficial for marketing teams looking to enhance their communication strategies with customers through social media platforms.